Clinical Outcome After Rectal Replacement With Side-to-End, Colon-J-Pouch, or Straight Colorectal Anastomosis Following Total Mesorectal Excision: A Swiss Prospective, Randomized, Multicenter Trial (SAKK 40/04). Issue 5 (May 2019) - Marti, Walter R.; Curti, Gaudenz; Wehrli, Heinz; Grieder, Felix; Graf, Michael; Gloor, Beat; Zuber, Markus; Demartines, Nicolas; Fasolini, Fabrizio; Lerf, Bruno; Kettelhack, Christoph; Andrieu, Christiane; et al.
Abstract : Objective: To compare, in a phase 3, prospective, randomized, multi-center clinical trial functional outcome of reconstruction procedures following total mesorectal excision (TME). Summary Background Data: Intestinal continuity reconstruction following TME is accompanied by postoperative defecation dysfunctions known as "anterior resection syndrome." Commonly used reconstruction techniques are straight colorectal anastomosis (SCA), colon J -pouch (CJP), and side-to-end anastomosis (SEA). Comparison of their functional outcomes in prospective, randomized, multi-center studies, including long-term assessments, is lacking. Methods: Patients requiring TME for histologically proven rectal tumor, with or without neoadjuvant treatment, age ≥ 18 years, normal sphincter function without history of incontinence, any pretreatment staging or adenoma, expected R0-resection, were randomized for standardized SCA, CJP, or SEA procedures. Primary endpoint was comparison of composite evacuation scores 12 months after TME. Comparison of composite evacuation and incontinence scores at 6, 18 and 24 months after surgery, morbidity, and overall survival represented secondary endpoints. Analysis was based on "per protocol" (PP) population, fully complying with trial requirements, and intention-to treat (ITT) population. Results: Three hundred thirty-six patients from 15 hospitals were randomized. PP population included 257 patients (JCP = 63; SEA = 95; SCA = 99). Composite evacuation scores of PP and ITT populations did not show statistically significant differences among the 3 groups at any time point. Similarly, composite incontinence scores for PP and ITT populations showed no statistically significant difference among the 3 trial arms at any time point. Conclusions: Within boundaries of investigated procedures, surgeons in charge may continue to perform reconstruction of intestinal continuity following TME at their technical preference. Abstract : Supplemental Digital Content is available in the text